High-fat diet improves tolerance to myocardial ischemia by delaying normalization of intracellular PH at reperfusion. (August 2019) - Inserte, Javier; Aluja, David; Barba, Ignasi; Ruiz-Meana, Marisol; Miró, Elisabet; Poncelas, Marcos; Vilardosa, Úrsula; Castellano, José; Garcia-Dorado, David
Abstract: Reports on the effect of obesity on the myocardial tolerance to ischemia are contradictory. We have described that obesity induced by high-fat diet (HFD) reduces infarct size in B6D2F1 mice submitted to transient coronary occlusion. In this study, we analysed the mechanism by which dietary obesity modifies the susceptibility to myocardial ischemia and the robustness of this effect. B6D2F1 (BDF), C57BL6/J (6J), C57BL6/N (6N) male mice and BDF female mice were fed with a HFD or control diet for 16 weeks. In all three strains, HFD induced obesity with hyperinsulinemia and hypercholesterolemia and without hyperglycemia, hypertension, ventricular remodelling or cardiac dysfunction. In obese mice from all three strains PDK4 was overexpressed and HSQC NMR spectroscopy showed reduced 13 C-glutamate and increased 13 C-lactate and 13 C-alanine, indicating uncoupling of glycolysis from glucose oxidation. In addition, HFD induced mild respiratory uncoupling in mitochondria from BDF and 6N mice in correlation with UCP3 overexpression. In studies performed in isolated perfused hearts submitted to transient ischemia these changes were associated with reduced ATP content and myocardial PCr/ATP ratio at baseline, and delayed pHi recovery ( 31 PNMR) and attenuated hypercontracture at the onset of reperfusion. Finally, in mice subjected to 45 min of coronary occlusion and 24 h of reperfusion, HFD significantly reduced infarct size respect to their respective control diet groups in male BDF (39.4 ± 6.1% vs. 19.9 ± 3.2%, P = 0.018) and 6N mice (38.0 ± 4.1 vs. 24.5 ± 2.6%, P = 0.017), and in female BDF mice (35.3 ± 4.4% vs. 22.3 ± 2.5%, P = 0.029), but not in male 6J mice (40.2 ± 3.4% vs. 34.1 ± 3.8%, P = 0.175) . Our results indicate that the protective effect of HFD-induced obesity against myocardial ischemia/reperfusion injury is influenced by genetic background and appears to critically depend on inhibition of glucose oxidation and mild respiratory mitochondrial uncoupling resulting in prolongation of acidosis at the onset of reperfusion. Highlights: HFD increases myocardial tolerance to ischemia in a strain-dependent way. HFD inhibits glucose oxidation and induces mild respiratory mitochondrial uncoupling. The resulting deficient energy metabolism delays pHi normalization at reperfusion. Delayed pHi recovery protects myocardium against reperfusion injury. Results could explain the better outcome observed in some obese patients with STEMI.